Reducing Mother-to-Child Transmission of HIV Using Quality Improvement Approaches. (14th June 2019) - Livesley, Nigel; Coly, Astou; Karamagi, Esther; Nsubuga-Nyombi, Tamara; Mwita, Stella Kasindi; Ngonyani, Monica M.; Mvungi, Jane; Kinyua, Kevin; Muange, Prisca; Ismail, Anisa; Quick, Timothy; Stern, Amy
Over half of mother-to-child HIV transmission (MTCT) occurs postdelivery. Keeping mother–infant pairs in care remains challenging. Health workers in 3 countries used quality improvement (QI) approaches to improve data systems, mother–infant retention, and facility-based care delivery. The number and proportion of infants with known HIV status at time of discharge from early infant diagnosis programs increased in Tanzania and Uganda. We analyzed data using statistical process control charts. Mother-to-child HIV transmission did not decrease in 15 Kenyan sites, decreased from 12.7% to 3.8% in 28 Tanzanian sites, and decreased from 17.2% to 1.5% in 10 Ugandan sites with baseline data. This improvement is likely due to the combination of option B+, service delivery improvements, and retention through QI approaches. Reaching the global MTCT elimination target and maximizing infant survival will require health systems to support mother–infant pairs to remain in care and support health workers to deliver care. Quality improvement approaches can support these changes.